An Academic-Community Collaboration to Deliver Medication Therapy Management (MTM) Services to Patients Living in Rural Counties of a Southwestern State in the United States. (October 2022) - Axon, David Rhys; Johnson, Melissa; Abeln, Brittany; Forbes, Stephanie; Anderson, Elizabeth J.; Taylor, Ann M.; Aseret-Manygoats, Teresa; Warholak, Terri; Hall-Lipsy, Elizabeth
Background: Patients living in rural communities often experience pronounced health disparities, have a higher prevalence of diabetes and hypertension, and poorer access to care compared to urban areas. To address these unmet healthcare service needs, an established, academic-based MTM provider created a novel, collaborative program to provide comprehensive, telephonic services to patients living in rural Arizona counties. Objective: This study assessed the program effectiveness and described differences in health process and outcome measures (e.g., clinical outcomes, gaps in care for prescribed medications, medication-related problems) between individuals residing in different rural-urban commuting area (RUCA) groups (urban, micropolitan, and small town) in rural Arizona counties. Methods: Subjects eligible for inclusion were 18 years or older with diabetes and/or hypertension, living in rural Arizona counties. Data were collected on: demographic characteristics, medical conditions, clinical values, gaps in care, medication-related problems (MRPs), and health promotion guidance. Subjects were analyzed using 3 intra-county RUCA levels (i.e., urban, micropolitan, and small town). Results: A total of 384 patients were included from: urban (36.7%), micropolitan (19.3%) and small town (44.0%) areas. Positive trends were observed for clinical values, gaps in care, and MRPs between initial and follow-up consultations. Urban dwellers had significantly lower average SBP values at follow-up than those from small towns (p < 0.05). A total of 192 MRPs were identified; 75.0% were resolved immediately or referred to providers and 16.7% were accepted by prescribers. Conclusion: This academic-community partnership highlights the benefits of innovative collaborative programs, such as this, for individuals living in underserved, rural areas.